The adaptability of Pseudomonas aeruginosa biofilm in oxygen-limited environments - Ren, Ling; Yuan, Yang; Farea, Khaled; Feng, Xu; He, Jia; Liu, Yi; Zheng, Bowen (Frontiers in Cellular and Infection Microbiology, 2025)
Under oxygen-limited conditions, the adaptability and underlying mechanisms of bacterial biofilms have become key areas of interest in microbiology and clinical infection research. Within biofilms—composed of bacterial communities and extracellular matrix—an oxygen gradient commonly forms, resulting in hypoxic or even anoxic microenvironments. Such conditions substantially increase biofilm antibiotic resistance and facilitate the persistence of chronic infections. This review systematically summarizes the adaptive strategies employed by biofilms in hypoxic environments, including anaerobic metabolism, phenazine-mediated electron shuttling, and virulence factor regulation. These adaptive responses are governed by genes involved in anaerobic metabolism, quorum sensing systems, and the secondary messenger 3,5-cyclic diguanylic acid (c-di-GMP), which collectively influence biofilm formation. Key transcriptional regulators such as Anr and Dnr, the two-component system NarXL, along with specific functional genes, form an intricate regulatory network. This article aims to provide a comprehensive overview of the adaptive mechanisms of Pseudomonas aeruginosa biofilms under oxygen-limited conditions, providing a theoretical foundation for the development of novel anti-infective therapies, targeting the biofilm infection microenvironment in cystic fibrosis and chronic wounds.